Role of disorders related to idiotypic and anti-idiotypic interactions in slowing down the achievement of negative serologic reactions in patients with early onset forms of syphilis after specific therapy - YE. N. Volkova; S. G. Morozov; YE. V. Mitichkina; A. A. Grigoriyeva; I. V. Yelistratova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To study the humoral immunity state in patients with the slowed down achievement of negative serologic reactions after the treatment of early onset forms of syphilis by means of examining the blood serum level of idiotypic and anti-idiotypic antibodies to cardiolipin and p17 Treponema Pallidum antigenic protein. Materials and methods. The study involved 324 patients (39.5% male and 60.5% female) with the slowed down achievement of negative serologic reactions. Primary (idiotypic) antibodies to cardiolipin and p17 protein were obtained using immunochromatographic assays with the help of the Bio Logik LP system. Purified antibodies were concentrated using the ultrafiltration technique with the aid of the XM-100А membrane. To obtain the rabbit antiserum to p17 Treponema Pallidum protein, chinchilla rabbits were immunized using the commercial recombinant p17 protein. To determine anti-cardiolipin idiotypic antibodies in the blood serum, the ELISa method optimized for detecting anti-cardiolipin antibodies was applied. To determine anti-cardiolipin anti-idiotypic antibodies as well as idiotypic and anti-idiotypic antibodies to p17 Treponema Pallidum protein, the standard ELISA method was applied. The following antigens were used to process the pads: F(ab)2 fragments of anti-cardiolipin antibodies (5 μg/mL), recombinant р17 T. pallidum protein (5 μg/mL) and F(ab)2 fragments of antibodies to р17 T. pallidum protein (10 μg/mL). The level of antibodies was assessed based on the absorbancy and expressed in conventional activity units using the K coefficient being the absorbancy of the serum under examination to the mean absorbancy of control serums ratio. The K value exceeding 1.5 conventional units indicated the increased level of antibodies. Results. Patients with the slowed down achievement of negative serologic reactions demonstrated a selective increase in the level of anti-idiotypic antibodies (AIAB) relative to T. pallidum antigens, cardiolipin and p17 protein, vs. first-order antibodies, which points at abnormal mutual regulation between idiotypic antibodies (IAB) and AIAB; the discovered phenomenon lays the immunochemical basis for the formation of a self-sustaining "vicious circle" contributing to the induction of high levels of antibodies to treponema antigens even when the pathogen was destroyed.